2013
DOI: 10.1371/journal.pone.0077111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2′-O-Methyl Nucleotide Substitution on EcoRI Endonuclease Cleavage Activities

Abstract: To investigate the effect of sugar pucker conformation on DNA-protein interactions, we used 2′-O-methyl nucleotide (2′-OMeN) to modify the EcoRI recognition sequence -TGAATTCT-, and monitored the enzymatic cleavage process using FRET method. The 2′-O-methyl nucleotide has a C3′-endo sugar pucker conformation different from the C2′-endo sugar pucker conformation of native DNA nucleotides. The initial reaction velocities were measured and the kinetic parameters, Km and Vmax were derived using Michaelis-Menten eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…S9, E to G). These kinetic properties are similar to those of other PD-D/E(X)K nucleases, such as Eco RI (27, 33). MIF also cleaved dsPS 30 (fig.…”
Section: Mif Cleaves 3′ Unpaired Bases Of Stem-loop Ssdnasupporting
confidence: 74%
“…S9, E to G). These kinetic properties are similar to those of other PD-D/E(X)K nucleases, such as Eco RI (27, 33). MIF also cleaved dsPS 30 (fig.…”
Section: Mif Cleaves 3′ Unpaired Bases Of Stem-loop Ssdnasupporting
confidence: 74%
“…Moreover, the unique nuclease selectivity of purified MIF protein on various DNA substrates with different structure or length of nucleotides at the 3' end reinforces the selectivity and potency of MIF's 3' nuclease activity. Although the kinetic analysis of MIF activity revealed a relatively slow reaction with t 1/2 at 7.7-10.8 min, K M at 0.7-0.9 μM and k cat at 0.02/min, it is comparable to some well-recognized nucleases including MutsS2, exoribonuclease (ExoN), ribozyme, and EcoRI [43][44][45][46][47] . For example, the nuclease activity of Thermus thermophilus MutS2 (ttMutS2), which is known to play an important role in MMR, has been reported to have a K M at 290 nM and k cat at 0.041/ min 44 , which are comparable to those of MIF.…”
Section: Discussionmentioning
confidence: 85%
“…For example, the nuclease activity of Thermus thermophilus MutS2 (ttMutS2), which is known to play an important role in MMR, has been reported to have a K M at 290 nM and k cat at 0.041/min 44 , which are comparable to those of MIF. The restriction nuclease EcoRI’s t 1/2 is 9.7 min calculated by UV linear dichroism 46 and about 8 min monitored by fluorescence changes 47 . As with many nucleases, it is possible that the additional enhancer may help MIF bind and cleave DNA efficiently in vivo, which requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…2′-F RNA and LNA locks sugar ring in C3′ endopucker conformation and has many advantages such as increasing affinity to RNA target 5,37) and protecting oligonucleotide against nuclease digestion 38) . In our previous study, we also found their applications in regulating endonuclease cleavage efficiency 39,40) . Though 2′-OMeRNA has similar characteristics of the C3′ endopucker conformation, it should be avoided in RCA application since it strongly suppressed RCA efficiency.…”
Section: Discussionmentioning
confidence: 97%